Scaling up Locally Adapted Clinical Practice Guidelines for Improving Childbirth Care in Tanzania: A Protocol for Programme Theory and Qualitative Methods of the PartoMa Scale-up Study - Jane Brandt Sørensen; Natasha Housseine; Nanna Maaløe; Ib Christian Bygbjerg; Britt Pinkowski Tersbøl; Flemming Konradsen; Brenda Sequeira Dmello; Thomas van Den Akker; Jos van Roosmalen; Sangeeta Mookherji; Eunice Siaity; Haika Osaki; et al. (Taylor & Francis Group, 2022)
Effective, low-cost clinical interventions to improve facility-based care during childbirth are critical to reduce maternal and perinatal mortality and morbidity in low-resource settings. While health interventions for low- and lower-middle-income countries are often developed and implemented top-down, needs and circumstances vary greatly across locations. Our pilot study in Zanzibar improved care through locally co-created intrapartum clinical practice guidelines (CPGs) and associated training (the PartoMa intervention). This intervention was context-tailored with health-care providers in Zanzibar and now scaled up within five maternity units in Dar es Salaam, Tanzania. This PartoMa Scale-up Study thereby provides an opportunity to explore the co-creation process and modification of the intervention in another context and how scale-up might be successfully achieved. The overall protocol is presented in a separate paper. The aim of the present paper is to account for the Scale-up Study's programme theory and qualitative methodology. We introduce social practice theory and argue for its value within the programme theory and towards qualitative explorations of shifts in clinical practice. The theory recognizes that the practice we aim to strengthen - safe and respectful clinical childbirth care - is not practiced in a vacuum but embedded within a socio-material context and intertwined with other practices. Methodologically, the project draws on ethnographic and participatory methodologies to explore current childbirth care practices. In line with our programme theory, explorations will focus on meanings of childbirth care, material tools and competencies that are being drawn upon, birth attendants' motivations and relational contexts, as well as other everyday practices of childbirth care. Insights generated from this study will not only elucidate active ingredients that make the PartoMa intervention feasible (or not) but develop the knowledge foundation for scaling-up and replicability of future interventions based on the principles of co-creation and contextualisation.